Análise dos níveis de ativídade física e burnoutem policiais militares - Deiveskan Serra Soares (2016)
The military police profession is a high risk activity, since these professionals deal in their daily lives, with situations of great stress including human conflicts. The literature suggests that the police are among the vulnerable professional burnout syndrome and that there are few studies investigating this syndrome and associate a coping strategy. The hypothesis of this study is that physical exercise can have a significant association in relation to Burnout functioning as protection element. This cross-sectional study with a quantitative approach, evaluated the levels of physical activity and the perception of the dimensions of burnout syndrome in a sample of military police in the city of Belo Horizonte. The sample consisted of 195 officers of both sexes and regardless of age. three instruments for data collection were used, each with a specific purpose. To identify the prevalence of Burnout in the police, the Burnout Inventory Maslach (MBI-HSS) was used, the level of physical activity was assessed by the International Physical Activity Questionnaire (IPAQ) and a sociodemographic questionnaire was used to collect demographicinformation and profile of participants. The results showed a high percentage of prevalence of Burnout syndrome (64%), especially among those classified with low level of physical activity and performing operational work activity. It is concluded that variables that refer to socio affective aspects influence the perception of this syndrome, having been through the variables that showed statistical significance, tracing a profile of sedentary police and vulneral burnout and found that the levels of physicalactivity are associated with Burnout indicators.